Free iron oxides modulate the surface properties of Benggang soil on Southern China: insights into erosive mechanisms - Jiang, Ling; Chen, Jie; You, Le-Xing; Jiang, Fang-Shi; Zhang, Yue; Lin, Jin-Shi; Huang, Yan-He (Frontiers in Environmental Science, 2024)
Benggang, an erosional phenomenon located in southern China, exhibits distinctive characteristics that can have profound ecological and agricultural consequences as well as pose risks to human life. Previous investigations have primarily focused on elucidating the relationships between the physical and chemical attributes of soils collected from Benggang. However, the precise role of free iron oxides in the surface properties of Benggang soil and its contribution to the formation of Benggang remains largely unexplored. In this study, we aim to investigate the role of free iron oxides in Benggang soil by removing them and subsequently introducing goethite to evaluate their impact on the soil's surface properties. Our results reveal a decrease in the surface charge density of soil colloidal particles with increasing soil depth. Specifically, the uppermost red soil layer exhibits the highest value, followed by the sandy soil and the lowermost clastic layer. Upon removing free iron oxide, we documented reductions of 44.28% (red soil), 20.62% (sandy soil), and 8.70% (clastic layer) in the surface charge density of colloidal particles. The red soil layer presented an over 18-fold increase compared to the initial linear shrinkage, followed by the sandy soil and clastic layer. Notably, the addition of goethite to the iron oxide-free soil layers resulted in the recovery of approximately 81.93%, 121.13%, and 104.35% of the initial surface charge density, respectively. Moreover, significant changes in volume shrinkage were observed, with approximately 97.54% (red soil), 94.75% (sandy soil), and 89.72% (clastic layer) of the initial values being influenced. These findings underscore the substantial influence of free iron oxide on the physicochemical properties of Benggang soil and contribute to a comprehensive understanding of the erosive mechanisms underlying Benggang formation.